Exploring the Values of Education through Post-Death Traditions in Indonesia - Japarudin, Japarudin; Fitria, Rini (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This research explores the values ​​of character education in post-death traditions in Indonesia. Post-death traditions play an important role in Indonesian culture and often reflect deep social values, ethics, and beliefs. This research involves an in-depth analysis of post-death traditions, including funeral ceremonies, memorial rituals, and related practices. The research method used in this research is library research and analysis of documents related to post-death traditions. It is hoped that the results of this research will provide a deeper understanding of the role of education in post-mortem traditions and how these values ​​can be integrated into the context of formal education in Indonesia. The findings of this research can provide new insights into how education and culture are interrelated, as well as how local traditions can contribute to the sustainable development of education in Indonesia. The character education values ​​ in the post-death ceremony tradition include religious, familial, and educational values. Educational values ​​include Religiosity, communicativeness, collaboration (cooperation), responsibility, and social concern.